Pembelajaran Pai Asyik Dan Menyenangkan Dengan Penggunaan Metode Number Head Together Di MTs Al Manar Jerrung Desa Lamatti Riawang - R.Nurhayati; Ummul Fauziah; Diarti Andra Ningsih; Irwin Hidayat; Sudirman P (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The role of learning methods is very important during the teaching and learning process. The success of learners' learning depends largely on the methods used by the teacher. Successful learning can be seen with the objectives of the learning contained in the Learning Implementation Plan (RPP) that has been formulated. In addition, learning methods and strategies play a role in activating students during the learning process, this is important so that students are not easily bored and understand the subject matter easily and are able to apply it in everyday life. The purpose of this service is to increase student activeness in discussing problems in learning they face. Learning results show that the method used is very effective as evidenced by the enthusiasm of students in participating in learning activities so that it can increase student enthusiasm for learning, especially in PAI subjects.